95.4k views
4 votes
Differentiating Exponential functions In Exercise,find the derivative of the function. See Example 2 and 3.

f(x) = (e^x + e^-x)4/2

User Bob Probst
by
5.6k points

1 Answer

3 votes

Answer: The derivative would be
f'(x)=2(e^(2x)-e^(-2x))

Explanation:

Since we have given that


f(x)=(e^x+e^(-x))^{(4)/(2)}\\\\f(x)=(e^x+e^(-x))^2

As we will use "Chain Rule"

and at last we will use the identity ''
a^2-b^2=(a-b)(a+b)''

We need to find the derivative of the function:


f'(x)=2(e^x+e^(-x))(e^x-e^(-x))\\\\f'(x)=2(e^(2x)-e^(-2x))

Hence, the derivative would be


f'(x)=2(e^(2x)-e^(-2x))

User Jasssonpet
by
6.1k points